The Effect of Pair Storytelling on Creative Writing Skills in Islamic Elementary Education - Atrianing Yessi Wijayanti; Antonius Nesi; Suntoro (JPI: Jurnal Pustaka Indonesia, 2026)
This study aimed to examine the effect of the paired storytelling learning model on the creative writing skills of fifth - grade students at Istiqomah Islamic Elementary School, West Ungaran District, Semarang Regency. A quantitative quasi - experimental design was employed using a nonequivalent control group design. The study involved all 68 fifth - grade students selected through saturated sampling, consisting of 33 students in class V A as the control group and 35 students in class V B as the experimental grou p. The independent variable was the paired storytelling learning model, while the dependent variable was students’ creative writing skills. Data were collected using a creative writing test and analyzed through prerequisite tests, including normality and homogeneity tests, followed by hypothesis testing using a t - test. The results showed that the paired storytelling learning model had a significant effect on students’ creative writing skills, as indicated by the t - count value, which was higher than the t - ta ble value (5.145 > 2.000). Therefore, the null hypothesis was rejected and the alternative hypothesis was accepted. These findings indicate that paired storytelling is an effective instructional model for improving elementary students’ creative writing skills. The study contributes empirical evidence that collaborative storytelling activities can support students in developing ideas, organizing narratives, and expressing imagination more creatively in written form.